STATE OF HEMOCOAGULATION AND IMMUNE STATUS IN THE CENTRAL AND REGIONAL BLOODSTREAM IN PATIENTS WITH ACUTE THROMBOSIS OF THE VEINS OF THE LOWER EXTREMITIES - Komiljonov Abdulazizbek Elmurodjon ugli (Western European Studies, 2024)
Acute thrombosis of the main veins is a severe, often life-threatening disease. The number of such patients not only does not decrease every year, but there is also a clear tendency towards their growth 3 After a certain time, 60-80% of patients develop postthrombophlebitic disease, and subsequently 15-29% develop trophic ulcers of the leg 2,4. All this often led to long-term incapacity and even disability for people of young working age 1. In recent years, the number of studies has increased indicating the participation of autoimmunoaggression in the process of venous thrombus formation, which contributes to the development and progression of venous insufficiency 2,3. In the initial stages of the disease, only the venous wall has antigenic properties, and with further progression of the pathological process, the tissues surrounding the vessel also have these qualities 1. Correction of hemocoagulation and immunological status of patients with thrombosis of the veins of the lower extremities will promote early recanalization and improve treatment results
Keywords: improve; status; patients